(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the nature of word stress in English, focusing on its acoustic and phonetic characteristics as well as its functional role in speech. The study analyzes the parameters that create syllable prominence—intensity, duration, fundamental frequency, and formant structure. Several types of stress are discussed, including dynamic, musical, quantitative, and qualitative, showing that English stress is a complex, multi-parameter phenomenon. Linguistically relevant degrees of stress are described: primary, secondary, and weak, with attention to the debated tertiary degree. The article also explains common patterns of stress placement in English, emphasizing the recessive and rhythmic tendencies typical for English phonological structure. Finally, distinctions between word stress and sentence stress are addressed. The study concludes that word stress is essential for lexical identification and intelligibility in English, especially in fast or unclear speech.